(untitled) (Journal of Environmental Science Studies, 2018)
The present work was carried out to study the air quality of Srinagar city and the samples were collected from five different sites which includes commercial area (site-I), industrial area (site-II), residential area (site-III), ecologically sensitive site (site-IV) and sensitive area (site-V). During the study samples were taken on monthly basis and were analyzed for nitrogen dioxide (NO ), sulphur dioxide (SO ) and repairable particulate matter 2 2 (PM ). Significant variation was recordedwithin and among the sites in NO (F = 3.82; F = 115, P < 0.05), 10 2 3 4 whereas among the sites in SO and PM (F = 167, P < 0.05) and (F = 72.55, P < 0.05) respectively. The study 2 10 4 4 revealed higher concentration of NO at Lal chowk which is commercial area and vehicular emission could be 2 the one of the reason for higher value of NO . SO exhibited high concentration at industrial area and could be 2 2 attributed to burning of fossil fuels in industries and use of generator sets. PM was also found higher in 10 industrial area due to presence of cement industries in addition to burning of coal as fuel. The overall concentration of NO and SO were found within the permissible limits for all sites as per National Ambient Air 2 2 Quality Standards (NAAQS) except for PM at site-I and site-II. The overall air quality index of site-I and 10 site-II falls within “Moderate” category and for site-III, IV and V falls within “Good” category.